2006
DOI: 10.1203/01.pdr.0000214894.18097.c4
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Dysfunction in Asphyxiated Newborn Piglets Resuscitated with 21% and 100% Oxygen

Abstract: Hemostatic disturbances are common in asphyxiated newborns after resuscitation. We compared platelet function in hypoxic newborn piglets reoxygenated with 21% or 100% oxygen. Piglets (1-3 d, 1.5-2.1 kg) were anesthetized and acutely instrumented for hemodynamic monitoring. After stabilization, normocapnic hypoxia was induced with an inspired oxygen concentration of 10 -15% for 2 h. Piglets were then resuscitated for 1 h with 21% or 100% oxygen, followed by 3 h with 21% oxygen. Platelet counts and collagen (2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Furthermore, in studies of term and near-term neonates, using 100% oxygen in the resuscitation has been associated with increased cardiac and renotubular damages [103] in addition to the increased oxidative stress shown in whole-blood markers (oxidized glutathione content) that persisted up to 28 days after birth [114] . In animal models of asphyxia, the increased oxidative stress has been related to impaired organ function and/or injury as in the heart, lung, brain, intestine, kidney, adrenal glands, and platelets [115][116][117][118][119][120][121] . Further, an epidemiological link between resuscitation with supplemental oxygen and childhood leukaemia has been suggested by Naumburg et al [122] and Spector et al [123] .…”
Section: Lowering Oxygen Concentrationsmentioning
confidence: 99%
“…Furthermore, in studies of term and near-term neonates, using 100% oxygen in the resuscitation has been associated with increased cardiac and renotubular damages [103] in addition to the increased oxidative stress shown in whole-blood markers (oxidized glutathione content) that persisted up to 28 days after birth [114] . In animal models of asphyxia, the increased oxidative stress has been related to impaired organ function and/or injury as in the heart, lung, brain, intestine, kidney, adrenal glands, and platelets [115][116][117][118][119][120][121] . Further, an epidemiological link between resuscitation with supplemental oxygen and childhood leukaemia has been suggested by Naumburg et al [122] and Spector et al [123] .…”
Section: Lowering Oxygen Concentrationsmentioning
confidence: 99%
“…57 Furthermore, the oxidative stress of pure oxygen lasts at least for 4 weeks after birth, 58 and there could be more myocardial and kidney injury. Animal studies have also shown that 100% oxygen activates transcription factors, leads to thrombocyte aggregation, 59 increases oxidative stress, neurologic and brain damage, 60,61 inflammation in the lung and heart and may also trigger pulmonary hypertension. 62 Finally, who would have imagined that only a few minutes of oxygen could be associated with childhood cancer?…”
Section: Tension Of Arterial Oxygen (Pao 2 )mentioning
confidence: 99%
“…These radicals can activate arachidonic acid metabolism with the production of thromboxane (Tx) A 2 and subsequent activation of platelets (4,5). Furthermore, hypoxia and reoxygenation are associated with increases in the plasma activities of matrix metalloproteinases (MMPs) 2 and 9 (6,7), which play an important role in the regulation of platelet aggregatory function (8,9). Platelet activation and dysfunction may be related to thromboembolic complications seen in asphyxiated newborns.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the platelet aggregatory response to collagen stimulation after life-threatening hypoxia and reoxygenation with 21% or 100% oxygen in an acutely instrumented animal model of neonatal asphyxia (7). Platelets were activated with increased plasma TxB 2 levels, and platelet aggregation was impaired similarly in both reoxygenated groups (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation